PENERAPAN SISTEM POINT OF SALE GUNA MEMBANTU PEMILIK TENANT MENGELOLA USAHA DI SOCIALSIP ULUWATU - I Komang Dwiprayoga; Made Agung Raharja; I Wayan Santiyasa (Jurnal Pengabdian Informatika, 2026)
The operation of sales and warehouse management at SOCIALSIP Uluwatu presents challenges for tenants in managing transactions and business operations efficiently. In this context, a web-based Point of Sale (POS) system becomes the primary solution to integrate transactions, simplify data processing, and enhance efficiency and security. This study aims to develop a POS system that meets the tenants' needs through various features, such as sales recording, inventory management, payment method integration, and data reporting. By adopting a tenant-centered development approach, this initiative not only provides a technological solution but also empowers tenants through improved digital literacy.